Lactic Acid Conversion to Acrylic Acid Over Fluoride-Substituted Hydroxyapatites - Wojcieszak, Robert; Bonnotte, Thomas; Paul, Sébastien; Katryniok, Benjamin; Dumeignil, Franck (Frontiers in Chemistry, 2020)
One of the most interesting intermediates for the chemical industry is acrylic acid, which can be derived from lactic acid by catalytic dehydration in the gas phase. The realization of this reaction is complex due to a strong thermal activation leading to the formation of undesired by-products (acetaldehyde, propanoic acid…) as well as polymerization. We studied this reaction over hydroxyapatites modified by substitution of the hydroxyl groups by fluoride. This notably enabled increasing the selectivity to acrylic acid while reducing the formation of the undesired acetaldehyde. Introduction of fluoride induced a modification of the phosphate (PO43-) groups. In the presence of water, fluoride prevented the formation of hydrogenophosphate species (HPO42-), which are well-known acid sites responsible for the formation of acetaldehyde by decarboxylation / decarbonylation. Further, we evidenced an important impact of fluoride substitution on crystallinity, specific surface area and on the surface Ca/P ratio. This latter is known to be a key parameter to control the acidity and the basicity of the hydroxyapatites. Using FT-IR spectroscopy with propyne as a probe molecule, we could show that lactic acid was concertedly adsorbed on basic and acid sites, which might be at the origin of the observed superior performances.